Impacts of grid-connected photovoltaic plant operation on the harmonic distortion - Batrinu, F.; Chicco, G.; Schlabbach, J.; Spertino, F. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
This paper illustrates and discusses some specific aspects concerning the harmonic distortion occurring in the operation of photovoltaic (PV) plants. The time evolution of the individual, total and partially weighted harmonic distortion is evaluated for a multistring PV plant and for a sun-shield installation affected by the consequences of the shading effect in the morning hours of the day